2018
DOI: 10.1103/physrevmaterials.2.035603
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of thermal transport anisotropy in stable glasses of vapor deposited organic molecules

Abstract: Vapour-deposited organic glasses are currently in use in many optoelectronic devices. Their operation temperature is limited by the glass transition temperature of the organic layers and thermal management strategies become increasingly important to improve the lifetime of the device. Here we report the unusual finding that molecular orientation heavily influences heat flow propagation in glassy films of small molecule organic semiconductors. The thermal conductivity of vapour-deposited thin-film semiconductor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…setting (κ xx +κ yy + κ zz )/κ T=320K =1. The resulting picture is consistent with experimental evidence [62] as shown in Fig. 4 where the thermal conductivity of the investigated TPD films is reported for three the different directions.…”
Section: Anisotropic Thermal Conductivitysupporting
confidence: 90%
See 2 more Smart Citations
“…setting (κ xx +κ yy + κ zz )/κ T=320K =1. The resulting picture is consistent with experimental evidence [62] as shown in Fig. 4 where the thermal conductivity of the investigated TPD films is reported for three the different directions.…”
Section: Anisotropic Thermal Conductivitysupporting
confidence: 90%
“…The calculated values of thermal conductivity resulted somewhat larger than those obtained experimentally. More specifically, at room temperature we get for the ISO sample 0.85 W m −1 K −1 to be compared with the experimental value 0.15 W m −1 K −1 [62]. This is very likely related to the adopted force-field, describing both intra-and intermolecular forces just approximately.…”
Section: Anisotropic Thermal Conductivitymentioning
confidence: 64%
See 1 more Smart Citation
“…23 To carry out this study, we have chosen the organic semiconductor TPD (N,N 0 -bis(3-methylphenyl)-N,N 0 -diphenylbenzidine), and the pharmaceutical molecule IMC (1-(4-Chlorobenzoyl)-5methoxy-2-methyl-3-indoleacetic acid), as they form glasses with enhanced stability and have been widely characterised as a function of deposition temperature. 2,3,15,16,22,[24][25][26][27][28][29][30] IMC shows a maximum of stability when deposited around 266 K (0.85T g ) 26 and a transition into the supercooled liquid governed in the first stages by a transformation front whose velocity depends on the deposition conditions of the IMC glass. 15,26 Spectroscopic ellipsometry measurements of thin film TPD glasses have shown that TPD also transforms via a propagating front under isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, it was recently reported that thermal conductivity in vapor‐deposited glasses is also correlated with molecular orientation, with the most efficient thermal transport occurring along the molecular long axes. [ 45 ]…”
Section: Discussionmentioning
confidence: 99%